A role for subducted super-hydrated kaolinite in Earth's deep water cycle. Issue 12 (December 2017) - Hwang, Huijeong; Seoung, Donghoon; Lee, Yongjae; Liu, Zhenxian; Liermann, Hanns-Peter; Cynn, Hyunchae; Vogt, Thomas; Kao, Chi-Chang; Mao, Ho-Kwang
Abstract Water is the most abundant volatile component in the Earth. It continuously enters the mantle through subduction zones, where it reduces the melting temperature of rocks to generate magmas. The dehydration process in subduction zones, which determines whether water is released from the slab or transported into the deeper mantle, is an essential component of the deep water cycle. Here we use in situ and time-resolved high-pressure/high-temperature synchrotron X-ray diffraction and infrared spectra to characterize the structural and chemical changes of the clay mineral kaolinite. At conditions corresponding to a depth of about 75 km in a cold subducting slab (2.7 GPa and 200 °C), and in the presence of water, we observe the pressure-induced insertion of water into kaolinite. This super-hydrated phase has a unit cell volume that is about 31% larger, a density that is about 8.4% lower than the original kaolinite and, with 29 wt% H2 O, the highest water content of any known aluminosilicate mineral in the Earth. As pressure and temperature approach 19 GPa and about 800 °C, we observe the sequential breakdown of super-hydrated kaolinite. The formation and subsequent breakdown of super-hydrated kaolinite in cold slabs subducted below 200 km leads to the release of water that may affect seismicity and help fuel arc volcanism at the surface. A super-hydrated clay mineral may play an important role in the solid Earth's water cycle, according to laboratory experiments. The mineral kaolinite can carry and release large amounts of water during subduction.